Penguatan Moderasi Beragama Sebagai Solusi Menyikapi Politik Identitas - Dandi Kurniawan; Abdullah A Afifi (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2023)
The sharp polarization caused by the general election in Indonesia has created a new phenomenon of intolerance which breaks unity and oneness. This polarization is also increasingly sharpened by the existence of elements that take advantage of this polarization for the interests of groups and classes, thus creating a climate of identity politics that is extreme left or right. Efforts to reduce this polarization need to be continuously developed. The development of religious moderation is an important step in addressing identity politics. Each party exists with various identities, both ethnicity, race and religion. Religious moderation plays a role in creating a conducive situation for each religion to grow and develop as one of the basic rights guaranteed by law. The author criticizes as well as provides suggestions from the results of a qualitative analysis of the literature on efforts to develop religious moderation. With the development of religious moderation, it is hoped that the polarization caused by identity politics will not become too extreme and disrupt the life of the nation and state.